Severe outcomes and risk factors of non-neutropenic fever episodes in hospitalized children with cancer in Kenya - Kipchumba, Samuel; Busby, Kenneth; Njenga, Dennis; Dettinger, Julia; Nyamusi, Lenah; Langat, Sandra; Olbara, Gilbert; Moyer, Cheryl A.; Vik, Terry A.; Nessle, C. Nathan; Njuguna, Festus (Frontiers in Oncology, 2025)
IntroductionCompared to febrile neutropenia (FN), non-neutropenic fever (NNF) episodes in children with cancer have not been associated with severe outcomes. Risk factors for severe outcomes in FN and NNF episodes in children with cancer from low-middle-income countries (LMIC) are incompletely described.MethodsA prospective, observational cohort study was conducted at a tertiary public referral hospital in western Kenya. Inclusion criteria were age ≤14 years, cancer diagnosis, hospitalized, fever >38.5°C or persistently >38°C. Neutropenia was an absolute count (ANC) <500 K/µL. Severe outcomes were BSI or death. Statistical analysis detected significance between groups and a univariate analysis was conducted.ResultsOf the 99 fevers, 54.5% were NNF episodes. Over 66% of NNF episodes were in patients with solid tumors. More severe outcomes were observed in NNF episodes compared to FN [BSI: 7.4% (4/54) vs. 4.4% (2/45); death: 7.4% (4/54) vs. 4.4% (2/45)], yet no deaths occurred in episodes with BSI. Acute leukemia not in remission (OR= 8.67, 95% CI [CI: 2.3-32.62]; p= 0.002) and concern for disease relapse (OR= 14.17, 95% CI [2.08-96.3]; p= 0.012) were significantly associated severe outcomes. Time to antibiotic administration (9 hours) did not differ by ANC. Under half (45.5%) of fever episodes had a blood culture ordered, with 93.9% obtained after administration of antibiotics.DiscussionNon-neutropenic fever episodes had more severe outcomes. Prompt fever management is recommended in all children with cancer treated in an LMIC setting. Pediatric oncology treatment centers in LMICs should rigorously evaluate their fever management clinical practice. Clinical risk factors were identified, but a risk-stratified approach in an LMIC setting is not recommended. Urgent attention is needed to identify areas of clinical improvement.